Evolution from Analogue to Digital Television in India: An Update of Stakeholders’ Subscription Revenues and Challenge - Kapoor, Arun Kumar; Mittal, Amit; Dhiman, Rahul (International Journal of Information Studies, 2025)
Digital television is a new buzzword in Indian entertainment & media industry. The limitations of analogue transmission brought the concept of digital television in India. The digital television is expected to bring more transparency in the system and better revenue sharing among the stakeholders. The present study makes an attempt to study the subscription revenues in the pre and post digitisation periods. For DAS-I the pre digitisation period taken is FY 2011-12 and post digitisation period is FY 2014-15. Similarly for Das-II pre digitisation period is FY 2012-13 and post digitisation period is FY 2015-16. Broadcasters Multi System Operators (MSOs) and Government are selected as key stakeholders in the present study. The other stakeholders such as Local Cable Operators (LCOs) are not considered due to unavailability of data. The study also addresses the challenges faced by the industry in the digitisation road map and various causes for unnecessary delays. The findings of the study indicates that the conversion from analogue to digital Television in India is successfully achieved in major cities in phase I and phase II, however subscription revenues of stakeholders are still to be seen a significant rise. Sociopolitical factors have caused unnecessary delays in Chennai and Coimbatore and have spoiled the smooth implementation of digital television. This as a result has provided big setback to the entertainment and media industry. The industry must gain knowledge from the faults of phase I & II and put improved methods and procedures in place. The complete mistrust between MSOs and LCOs is one of the biggest reasons for the stumbling pace of digital switchover. The study suggests that the role of government is also crucial and should set up a digital switchover support, which could spread awareness and rewards stakeholders who are the part of making the switchover a success.